Обработка сигнала ЭМГ на основе частотно-временнго метода для терапии - Прасол, И. В.; Ерошенко, О. А. (ХНУРЭ, 2017)
It is proposed to use the information frequency-time method of EMG analysis to obtain a qualitative and quantitative assessment of the human neuromuscular system state for selecting the optimal parameters of stimulating effects during electrotherapeutic massage procedures. It allows to increase the effectiveness of therapy and reduce the duration.
Keywords: биомединженерия; ЭМГ; терапия